Propagation of waves in the layer of a thermo-viscoelastic transversely isotropic medium - Gupta, Rajani Rani; Gupta, Raj Rani (Zielona Góra: Uniwersytet Zielonogórski)
The article is presented to enhance our knowledge about the propagation of Lamb waves in the layer of a viscoelastic transversely isotropic medium in the context of thermoelasticity with GN theory of type-II and III. Secular equations for symmetric and skew-symmetric modes of wave propagation in completely separate terms are derived. The amplitudes of displacements and temperature distribution were also obtained. Finally, the numerical solution was carried out for cobalt and the dispersion curves, amplitudes of displacements and temperature distribution for symmetric and skew-symmetric wave modes are presented to evince the effect of anisotropy. Some particular cases are also deduced.
Keywords: viscoelastic; thermoelasticity; phase velocity transversely isotropic